2023
DOI: 10.1101/2023.12.14.571608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA-guided RNA silencing by an Asgard archaeal Argonaute

Carolien Bastiaanssen,
Pilar Bobadilla Ugarte,
Kijun Kim
et al.

Abstract: Eukaryotic Argonaute proteins achieve gene repression and defense against viruses and transposons by RNA-guided RNA silencing. By contrast, known prokaryotic Argonautes adopt single-stranded DNA as guides and/or targets, leaving the evolutionary origin of RNA-guided RNA silencing elusive. Here, we show an evolutionary expansion of Asgard archaeal Argonautes (asAgos), including the discovery of HrAgo1 from the Lokiarchaeon ‘CandidatusHarpocratesius repetitus’ that shares a common origin with eukaryotic PIWI pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Previous studies of representative proteins from various subclades of long-A pAgos demonstrated that most of them act as DNA-guided DNA nucleases (DNA > DNA pAgos) ( 12 , 15–19 , 30–32 ), with small groups of DNA-guided RNA nucleases (DNA > RNA pAgos, including PliAgo, PnyAgo and MbpAgo) ( 33 , 34 ) and the RNA-guided DNA nucleases from thermophilic bacteria mentioned above (RNA > DNA pAgos, including MpAgo and TmAgo) ( 22 ) (Figure 1B ). An RNA-guided pAgo that recognizes RNA targets (RNA > RNA pAgo) was discovered very recently in thermophilic Asgard archaea ( 35 ). While in vitro activities of these pAgos have been studied in much detail, their functional analysis in vivo has been limited to just a few proteins, all of which are DNA-guided DNA nucleases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of representative proteins from various subclades of long-A pAgos demonstrated that most of them act as DNA-guided DNA nucleases (DNA > DNA pAgos) ( 12 , 15–19 , 30–32 ), with small groups of DNA-guided RNA nucleases (DNA > RNA pAgos, including PliAgo, PnyAgo and MbpAgo) ( 33 , 34 ) and the RNA-guided DNA nucleases from thermophilic bacteria mentioned above (RNA > DNA pAgos, including MpAgo and TmAgo) ( 22 ) (Figure 1B ). An RNA-guided pAgo that recognizes RNA targets (RNA > RNA pAgo) was discovered very recently in thermophilic Asgard archaea ( 35 ). While in vitro activities of these pAgos have been studied in much detail, their functional analysis in vivo has been limited to just a few proteins, all of which are DNA-guided DNA nucleases.…”
Section: Introductionmentioning
confidence: 99%